MODELLING OF MAGNETIC REGENERATOR AND HEAT TRANSFER AGENT IN MICROCHANNELS - Botoc, Dorin; Oneata, Bianca Eliza; Rusu, Ionut; Salceanu, Alexandru; Avsec, Jurij (Journal of Energy Technology, 2024)
In this article, a brief introduction of conventional refrigeration is given, followed by a description and history of magnetic refrigeration. The active magnetic regenerator comprises 12 parallel plates of ma- gnetocaloric material (gadolinium (Gd)), through which circulates the heat transfer fluid (water, in this case). At both ends of the regenerator are the heat exchangers. The hot heat exchanger (HHEX) and the cold heat exchanger (CHEX) connects the fluid to the heat sources. The principle of operation of a magnetic refrigeration installation is based on exploiting the magnetocaloric effect from the materials that possess these properties (in this case, Gd).